Interactive Computer-Video Modules for Health Sciences Education - McArthur, J. R.; Bolles, J. R.; Fine, J.; Kidd, P.; Bessis, M. (Methods of Information in Medicine, 1989)
Advances in electronic image recording and computer technologyhave resulted in a remarkable increase in the power and flexibility of interactive computer-video teaching systems. The University of Washington Health Science Videodisc Development Group first demonstrated a laser videodisc controlled by a remote central computer in 1980. Even this rudimentary unit highlighted basic medical informatics principles including: rapid accessibility; a “generic” or multi-purposed format; ease of computer control; and large collections of valid, rigorously reviewed images. Advances in medical informatics have led to the development of the following previously undescribed series of teaching units:1. The hypertext programs Hypercard, Linkway, and Guide have been used with videodiscs to develop easy-to-use instructional and reference materials. These materials demonstrate the ease with which a computer-naive instructor may develop new programs and the advantage that the intuitive nature of these programs brings to student users.2. Patient simulations using single and double screens plus pre-defined knowledge structures;3. Interactive single topic tutorials using preset knowledge structures;4. A key-word-based disc searching system;5. Electronic video microscopy;6. A series of programs developed independently by health science faculty who have purchased multi-purpose videodiscs that demonstrate the flexibility of the multi-purpose or “generic”: collection concept.
Keywords: Computer Simulation; Programming Languages; Computerized Voice and Video; Optical Disks; Health Education